Hiding in plain sight: The global implications of manager disclosure - Evans, Richard B. (2022)
Given the potential for agency conflicts in delegated asset management, and the constant push for disclosure by regulators, we examine a clear potential source of agency conflicts in the mutual fund industry: anonymously managed mutual funds. Using a global sample of mutual funds, we find that 17% of funds worldwide, excluding the US, and 22% of emerging market funds do not disclose the names of their management team. Anonymously managed funds significantly underperform, have lower active share, return gap, tracking error, and higher r2 than funds with named managers. They are more frequent in families with cooperative structures, and in bank affiliated funds. Further examining fund performance and activity around changes in SEC disclosure regulation, we find that both performance and fund activity increases following new regulation that required disclosure of manager names. This is important, as it provides evidence that the underperformance of anonymous teams is related to the disincentive brought on by anonymous management, and not solely due to less skilled managers being kept anonymous.